The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/v12060675
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Symbiosis Primes Tolerance to Cucumber Mosaic Virus in Tomato

Abstract: Tomato plants can establish symbiotic interactions with arbuscular mycorrhizal fungi (AMF) able to promote plant nutrition and prime systemic plant defenses against pathogens attack; the mechanism involved is known as mycorrhiza-induced resistance (MIR). However, studies on the effect of AMF on viral infection, still limited and not conclusive, indicate that AMF colonization may have a detrimental effect on plant defenses against viruses, so that the term “mycorrhiza-induced susceptibility” (MIS) has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 70 publications
(91 reference statements)
0
6
0
1
Order By: Relevance
“…In return, the AMF assist the host plant in the acquisition of water and mineral nutrients, becoming extremely important for the uptake of inorganic phosphate, nitrogen and various micronutrients (Smith and Smith, 2011 ; Hodge and Storer, 2015 ; Ezawa and Saito, 2018 ). In addition, AM symbiosis also result in an enhanced ability of the host plant to overcome adverse conditions, including abiotic and biotic stress factors ( Sánchez-Bel et al , 2016 ; He et al , 2017 ; Rivero et al , 2018 , Fracasso et al , 2020 ; Miozzi et al , 2020 ; Sanmartín et al , 2020a; b ).…”
Section: Introductionmentioning
confidence: 99%
“…In return, the AMF assist the host plant in the acquisition of water and mineral nutrients, becoming extremely important for the uptake of inorganic phosphate, nitrogen and various micronutrients (Smith and Smith, 2011 ; Hodge and Storer, 2015 ; Ezawa and Saito, 2018 ). In addition, AM symbiosis also result in an enhanced ability of the host plant to overcome adverse conditions, including abiotic and biotic stress factors ( Sánchez-Bel et al , 2016 ; He et al , 2017 ; Rivero et al , 2018 , Fracasso et al , 2020 ; Miozzi et al , 2020 ; Sanmartín et al , 2020a; b ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Khoshkhatti et al ( 2020 ) found that Rhizoglomus irregularis inoculation of tomato plants significantly decreased the Tomato bushy stunt virus (TBSV) symptoms of young plant leaves as compared to non-inoculated ones at 20 dpi. Also, Miozzi et al ( 2020 ) investigated the effect of F. mosseae colonization on tomato infection with cucumber mosaic virus (CMV) at 14 dpi. They demonstrated that infected plants had much more severe viral symptoms and had a threefold higher average DS than AM plants.…”
Section: Resultsmentioning
confidence: 99%
“…Estudos realizados por Spagnoletti et al (2020), demonstram que a severidade da doença da podridão radicular do carvão na soja, causada pelo fungo Macrophomina phaseolina, foi reduzida nas plantas em que houve inoculação com fungos micorrizicos, Rhizophagus intraradices além disso, aumentou a biomassa dessas plantas comparadas as plantas que não apresentavam simbiose. Miozzi et al (2020), observaram o efeito da colonização de FMA da espécie Funneliformis mosseae na infecção pelo vírus do mosaico do pepino (CMV) no tomate, mostrando que o estabelecimento de uma simbiose funcional é capaz de limitar o desenvolvimento dos sintomas, mitiga a redução de genes relacionados a fotossíntese, também acarreta num aumento de ácido salicílico e uma modulação de genes que limitam o acúmulo de espécies reativas de oxigênio, denominando de efeito priming. Song et al (2015), relataram tolerância a Alternaria solani e Fusarium oxysporum em associações micorrízicas na cultura do tomateiro.…”
Section: Micorrizas E Seus Impactos Na Tolerância De Doenças Em Plantasunclassified